THE IMPACT OF TOP MANAGEMENT FEATURES ON SOUTH ALABAMA CONSTRICTIONS COMPANIES' FIRM PERFORMANCE: THE ROLE OF BOARD SIZE AS A MODERATOR - Tariq Tawfeeq Yousif Alabdullah; Madziatul Churiyah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Understanding the impact of top management on South Alabama's construction firms is vital. This study investigates the relationship between specific top management traits, with a focus on gender diversity, and the financial performance of these businesses from 2018 to 2021. Using regression analysis, we assess top management's influence and explore whether board size moderates this relationship. Preliminary findings suggest that larger top management teams have a statistically significant, though negative, effect on corporate performance. The research also underscores the significance of top management's financial background and the presence of women in managerial roles on company performance. This study's uniqueness lies in its exclusive focus on South Alabama's construction industry, providing valuable insights. It assists businesses in making informed decisions about leadership and governance structures for long-term success. Policymakers can benefit by understanding how top management traits and gender diversity affect business success, informing diversity and inclusion initiatives in corporate leadership. Shareholders and investors can gain a deeper understanding of top management's role in performance, aiding investment decisions. Identifying key success factors supports strategic planning to maximize shareholder value. This study offers valuable insights into South Alabama's construction industry, enhancing our understanding of top management's impact on performance. By examining the interplay between top management traits, board dynamics, and company performance, it provides practical insights for improved decision-making, diversity, and long-term industry development.